2019
DOI: 10.1186/s12909-019-1693-9
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of the WReN spider, an instrument to measure health professionals’ experience of research: a bibliographic study

Abstract: Background In 1997 the “Wessex Research Network (WReN) Spider” was developed and validated to assess the research experience of general practice based researchers. This bibliometric study traces the use and development of this instrument over 15 years. Methods We performed a bibliographic search to identify all the citations of the original article since 2002. Results Thirty one relevant papers were found. Publications were classified accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The impacts reported in the included articles were largely qualitative reports. Some studies incorporated quantitative data capture tools, such as the Research Capacity and Culture tool [ 48 , 49 ] and the WReN (Wessex Research Network) spider [ 50 , 51 ], or counts of publications, presentations and awards. The quantitative measures appeared to explore a discrete component of research impact, whereas the qualitative data provided a broad picture of the impacts in different contexts and uncovered both intended and unintended consequences of the research activity.…”
Section: Discussionmentioning
confidence: 99%
“…The impacts reported in the included articles were largely qualitative reports. Some studies incorporated quantitative data capture tools, such as the Research Capacity and Culture tool [ 48 , 49 ] and the WReN (Wessex Research Network) spider [ 50 , 51 ], or counts of publications, presentations and awards. The quantitative measures appeared to explore a discrete component of research impact, whereas the qualitative data provided a broad picture of the impacts in different contexts and uncovered both intended and unintended consequences of the research activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, although interviewees suggested that research engagement should be captured through quantitative data on the number of registered projects (audit, quality, improvement and research) and individuals involved in these projects, no one mentioned using existing measures of research awareness/engagement such as research spider or research culture and capacity survey, which have been reported in other NMAHPP clinical academic contexts. [48][49][50] It is possible that measures of actual research activity held greater importance for interviewees compared with more abstract measures of research knowledge and research intention; however, it is also possible that interviewees were not aware of the existing survey measures.…”
Section: Open Accessmentioning
confidence: 99%
“…50 The original version of the tool assessed only one construct: experience. Other constructs have since been added 51 including interest 52 and confidence. 53 Ried et al 54 extended the instrument to understand desired research skills.…”
Section: Data Collectionmentioning
confidence: 99%